2022
DOI: 10.2174/18742858-v16-e2208180
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Multidrug-resistant Bacterial Uropathogens and Associated Factors in Urinary Tract Infection Suspected Adult HIV-Positive Patients in Southern Ethiopia

Abstract: Background: Due to the reduction of their immunity, people living with the human immunodeficiency virus (HIV) are more susceptible to acquiring urinary tract infections (UTI). Moreover, the emergence of drug-resistant bacterial uropathogens has grown widely and now constitutes a severe clinical problem among HIV-positive patients. Methods: An institution-based cross-sectional study was conducted at the ART clinic of Arba Minch General Hospital from 1st January to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…Nevertheless, only a lower extent of MDR was reported from northern part of Ethiopia [ 21 ], and Nepal [ 33 ]. The present study also revealed that a higher prevalence (76.2%) of MDR was shown by GNB, which is in line with the results of a couple of studies done in Ethiopia (Bahir Dar and Arba Minch) [ 22 , 40 ]. In contrast, a higher prevalence of MDR among Gram-positive strains was reported by a couple of previous studies done in Ethiopia [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Nevertheless, only a lower extent of MDR was reported from northern part of Ethiopia [ 21 ], and Nepal [ 33 ]. The present study also revealed that a higher prevalence (76.2%) of MDR was shown by GNB, which is in line with the results of a couple of studies done in Ethiopia (Bahir Dar and Arba Minch) [ 22 , 40 ]. In contrast, a higher prevalence of MDR among Gram-positive strains was reported by a couple of previous studies done in Ethiopia [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…aureus were MRSA. This trend was by and large similar to a recent study conducted among HIV patients in the study area, Arba Minch [ 40 ]. However, it is on the higher side in comparison to the outcome of previous studies conducted in Bahir Dar [ 22 ] and Arba Minch [ 41 ], Ethiopia where the resistance observed was only 33.3 and 42.5% respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The permanence of HIV patients in hospitals increases the risk of nosocomial transmission of virulent microorganisms, which can migrate into and out of the hospital environment (Panis et al, 2009 ). E.coli, K. pneumoniae, P. mirabilis, P. aeruginosa, S. aureus , and S. saprophyticus are the most common bacterial etiologies of UTI (Panis et al, 2009 ; Marami et al, 2019 ; Simeneh et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%